TRPC3 inhibition induces myofibroblast differentiation in diabetic dermal fibroblasts - Toogood, Gemma; Evans, Robin; Zhang, Liping; Patel, Rima; Meng, Songmei; Boda, Vijay K.; Li, Wei; Xu, Junwang (Frontiers in Physiology, 2025)
Diabetic wounds present a significant healthcare challenge due to impaired healing mechanisms, with dermal fibroblasts playing a crucial role in tissue repair. This study investigates the role of transient receptor potential canonical-3 (TRPC3) in the dysfunction of diabetic fibroblasts and explores the therapeutic potential of TRPC3 inhibition. Findings reveal that TRPC3 expression is significantly elevated in diabetic dermal fibroblasts, which correlates with suppressed transforming growth factor-beta (TGF-β) signaling and impaired differentiation into myofibroblasts. Inhibiting TRPC3 effectively restores fibroblast functionality by upregulating TGF-β1 and its downstream effector, SMAD4. This restoration enhances the expression of key myofibroblast markers, such as α-smooth muscle actin (ACTA2) and type I collagen (COL1a1), which are essential for wound contraction and extracellular matrix remodeling. These results establish TRPC3 as a critical regulator of fibroblast activity and present TRPC3 inhibition as a promising therapeutic strategy for improving wound healing in diabetic patients.